Building of the Simile in Dar'iat Abi Alaa Al- Marie - Al- Sharif, Haneen Shaker (Arab Journal for Sciences and Research Publishing, 2022)
This study dealt with the building of the Simile in Dar'iat Abi Alaa Al- Ma’arri. Dar'iat means Poems that describe the armor. It has been printed and attached to the divan of (Saqt Al- Zand), in which Al- Ma’arri describes the armor and its benefits. The importance of such theme is attributed to the quality of the literary material within the Second Abbasid era. Also, it refers to that Abi Al- Alaa Al- Ma’arri – Despite him being blind- has a special character in building of the Figure of speech. Although such divan is small in size, it considered to be a Fertile ground for study as the poetic text in it is full with the varied rhetoric secrets. The aim of this study is to apply this theoretical rhetoric lesson, as well as identify the elements of creativity in meanings building at Al- Ma’arri. Also, it aims to highlight his experience via his formation to the Figure of speech and the role of the art of figures of speech in meaning formations.The study was based on two sections, the first dealt with the theoretical side of the study with a brief look at the life of Al- Ma’arri and Dar'iat and the Figure of speech and its importance.The second section is the practical aspect, dealing with the building of the SimileThe study reached to that Dar'iat was one of the best models that provided by Al- Ma’arri, and it represents his attitude towards isolation, and this isolation reflected in his phrases.
Keywords: Al-Ma'arri; The Shields; Simile